IGARSS 2008 - 2008 IEEE International Geoscience and Remote Sensing Symposium 2008
DOI: 10.1109/igarss.2008.4780059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ALOS-PALSAR for Ice Monitoring - What Can L-band do for the North American Ice Service?

Abstract: The Canadian Ice Service (CIS), the U.S. National Ice Center (NIC), and the International Ice Patrol (IIP), partners in the North American Ice Service (NAIS), have individually and jointly used airborne and spaceborne synthetic aperture radar data extensively for almost three decades in their daily ice monitoring operations. SAR's unique ability to penetrate clouds and weather make these data invaluable to the NAIS' efficient environmental stewardship and safe operation in Canadian and U.S. waters. Since 1992,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…The ALOS-2 images on the other hand (Figure 6b,c) show a lot more OI in the FYI section compared to the sea ice chart. With its higher penetration depth, the L-band signal detects more internal structures within the more malleable FYI [10]. In order to assess the potential error of OI detection in FYI areas, the previously trained RF classifiers which were used to classify the 5 April and 28 April ALOS-2 images were reapplied on the SPAN and H parameters of the ALOS-2 image over Hudson Bay (Figure 1) and results are shown in Figure 6d.…”
Section: Classification and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The ALOS-2 images on the other hand (Figure 6b,c) show a lot more OI in the FYI section compared to the sea ice chart. With its higher penetration depth, the L-band signal detects more internal structures within the more malleable FYI [10]. In order to assess the potential error of OI detection in FYI areas, the previously trained RF classifiers which were used to classify the 5 April and 28 April ALOS-2 images were reapplied on the SPAN and H parameters of the ALOS-2 image over Hudson Bay (Figure 1) and results are shown in Figure 6d.…”
Section: Classification and Validationmentioning
confidence: 99%
“…Most of the early sea ice classification studies were conducted using single polarized C-band SAR data from ERS-1 [2][3][4][5], ERS-2 [6][7][8] and RADARSAT-1 [1,[8][9][10][11]] SAR systems. The first multifrequency fully polarimetric SAR measurements over sea ice were airborne SAR data acquired in 1988 and introduced in [12].…”
Section: Introductionmentioning
confidence: 99%
“…Both optical and microwave remotely sensed data, for example, advanced very-high-resolution radiometer, Landsat, Moderate Resolution Imaging Spectroradiometer Onboard Terra and Auqa (MODIS), Advanced Microwave Scanning Radiometer-EOS, Envisat, and Radarsat (Arkett et al, 2008;Cavalieri et al, 2006;Kern et al, 2007;Lythe et al, 1999;Ochilov & Clausi, 2012;Ramsay, 1998;Scheuchl et al, 2001;Spreen et al, 2008), have been used to identify sea ice and subsequently used to produce sea ice concentration maps. Both optical and microwave remotely sensed data, for example, advanced very-high-resolution radiometer, Landsat, Moderate Resolution Imaging Spectroradiometer Onboard Terra and Auqa (MODIS), Advanced Microwave Scanning Radiometer-EOS, Envisat, and Radarsat (Arkett et al, 2008;Cavalieri et al, 2006;Kern et al, 2007;Lythe et al, 1999;Ochilov & Clausi, 2012;Ramsay, 1998;Scheuchl et al, 2001;Spreen et al, 2008), have been used to identify sea ice and subsequently used to produce sea ice concentration maps.…”
Section: Remote Sensing Data Usage and Methodologymentioning
confidence: 99%
“…[1] into it's usability for operational services. Multiple studies have shown that L-band SAR can provide better contrast between different sea ice types and can provide complimentary information [1,2], such as detecting and separating deformed sea ice from the surrounding sea ice [2] and provide easier separation between first year ice (FYI) and multi-year ice (MYI) in the early and advanced melt season [2]. It was reported by [3] that L-band SAR could separate MYI among second year ice (SYI) during dry ice winter conditions.…”
Section: Introductionmentioning
confidence: 99%